Understanding competition policy a suggested framework - Medalla, Erlinda M. (2003)
This paper defines the elements that comprise a competitive setting and clarifies the objectives of competition policy. The role and primary task of competition policy are emphasized. A framework for competition policy and the basic elements to implement it are spelled out. The major areas of competition policy are also identified and current competition policies in selected countries are briefly surveyed. The concluding section addresses some of the issues that confront competition policy.
This paper was presented during the Pacific Trade and Development (PAFTAD) Conference, held on 16-18 September 2002 at the AIM Conference Center, Makati City, Philippines.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 22-23).
Keywords: Competition, Unfair -- Philippines; Competition -- Government policy -- Philippines; Anti-trust law -- Philippines; Restraint of trade